Eksplorasi Kemampuan Abstraksi Matematis Siswa SMP Negeri 2 Kajen dalam Materi Geometri Serta Implikasinya dalam Pembelajaran - Sabita, Nadia Risqi; Pramesti, Santika Lya Diah (Universitas PGRI Semarang, 2026)
This study aimed to explore the mathematical abstraction abilities of eighth-grade students at SMP Negeri 2 Kajen in the context of solid geometry, and to identify implications for instructional practice. A descriptive qualitative approach was employed, with three students selected through purposive sampling to represent a range of mathematical proficiency levels: high (S1), high-to-moderate (S2), and moderate (S3). Data were gathered through classroom observation and in-depth interviews, analysed using the Miles and Huberman framework, and validated through method triangulation. Abstraction ability was examined across four indicators adapted from Dreyfus (1991): representation, identification of geometric properties and elements, classification, and generalisation. Findings revealed a consistent gradient aligned with the cognitive hierarchy of the indicators: representation and property identification were relatively more developed than classification and generalisation. S1 demonstrated proficiency across all four indicators independently; S2 handled representation well but required prompting for abstract classification and generalisation; S3 could only operate at the visual level for representation and identification, while classification and generalisation had yet to emerge. Teacher-centred instruction and limited use of hands-on manipulatives were found to constrain the development of higher-order abstraction abilities. The study recommends incorporating open-ended questioning, integrating digital geometry tools, and applying adaptive scaffolding as strategies to progressively support the growth of mathematical abstraction in junior high school students.